Association between physical activity and general health status in elderly people of the city of Talca during the confinement by pandemic (Revista Chilena de Rehabilitación y Actividad Física, 2022)
Introduction: The effect of the prolonged confinement generated by the pandemic had the consequence that a large number of older people (PM) stopped attending the physical activity program of the House for the Elderly (CAM) in the city of Talca. Objective: To correlate physical activity levels and general health status in PM during confinement. Methodology: Non-experimental correlational study. The selection of the sample was considering all the PMs who stopped regularly attending the physical activities organized by the CAM. The IPAQ and EQ-5D questionnaires were applied via mail or by telephone, the measurement of the relationship between variables was by means of Pearson’s correlation. In all cases, a p < 0.05 was adopted and the calculations were made in SPSS 27. Results: The participants were 60 subjects (lack of average age and SD), there was a significant correlation between the level of physical activity and health status indicators such as such as: mobility, personal care and ADL (p < 0.05), however, there was no correlation between the level of physical activity and pain, discomfort, anxiety, depression and self-perceived health (p < 0.05). Conclusion: In conditions of confinement, there is a correlation between PA and functional conditions such as mobility, personal care and ADL.
Keywords: Physical Activity; Health Status; Older People; Confinement; IPAQ; EQ-5D